DI-014 Continuing use of outpatient prescription drugs in patients hospitalised on a cardiology ward does not improve medication knowledge. (25th February 2017) - Engel-Dettmers, E; Smit, D; Damhof, M
Abstract : Background: During hospitalisation, the distribution of outpatient prescription drugs is taken over by the hospital pharmacy, and medication is administered by the nurse. Research shows that after hospitalisation, medication knowledge of patients is diminished compared with knowledge before admission, and more than 50% of patients do not know if there have been medication changes during hospitalisation. Purpose: We hypothesised that the use and management of their own outpatient prescription drugs in patients hospitalised on a cardiology ward will improve medication knowledge on correct use of prescribed medicines by 30% compared with standard care. Material and methods: Patients admitted to the cardiology ward between April and June 2016 meeting the inclusion criteria were enrolled in this study. Patients received either standard care (control group) or were allowed to continue and manage their outpatient prescription drugs (intervention group). In the intervention group, new prescription drugs were provided by the pharmacy practitioner on the ward and extra information about the drug use was provided. A questionnaire about drug knowledge and perception was applied twice, before the start of hospitalisation and after discharge. Results: 26 patients received standard care and 26 patients were allowed to continue and manage their outpatient prescription drugs. Knowledge of indication and correct medication use between the control and intervention groups was not significantly different. However, patients in the intervention group were more satisfied about the information provided by the pharmacy practitioner compared with patients who received standard care, 6.6 vs 7.6, respectively, on a 10 point grading scale (p=0.001). Conclusion: Continuing use and self management of outpatient prescription drugs did not improve medication knowledge in patients hospitalised on a cardiology ward. However, patients who continued and managed their outpatient prescription drugs were more satisfied. This study shows that in this patient population other interventions are needed to improve medicine knowledge. References and/or acknowledgements: Ziaeian B, Araujo KL, Van Ness PH, et al. Medication reconciliation accuracy and patient understanding of intended medication changes on hospital discharge. J Gen Intern Med2012;27:1513–20. Pasina L, Brucato AL, Falcone C, et al . Medication non-adherence among elderly patients newly discharged and receiving polypharmacy. Drugs Ageing 2014;31 :283–9. No conflict of interest